CHARACTERISTICS OF YOUNG WOMEN PERFORMING EARLY MARRIAGE - Masruroh Masruroh; Agus Susanto; Eko Mindarsih (POLTEKKES KEMENKES JAYAPURA, 2022)
The prevalence of marriage in Indonesia is quite high. Most of the perpetrators of early marriage come from rural areas and are triggered by many factors. Some of these triggering factors come from the lack of knowledge and attitudes of early marriage actors. In addition, early marriage is also triggered by external factors such as community culture, poverty, family roles, and dropping out of school. The purpose of this study is to explore the background of young women who are perpetrators of early marriage. This study uses a qualitative approach with a variety of phenomenology. Field data collection was carried out in January - February 2020. Researchers conducted research in Ponjong and Playen Districts, Gunungkidul Regency, Yogyakarta Special Region Province. Field data collection was carried out through semi-structured in-depth interviews and observations. Researchers triangulated sources and methods to ensure the validity of field data. Data analysis and presentation adopt data analysis from Miles and Huberman. Field findings show that the majority of young women who marry early come from complete families, have low economic backgrounds, live in villages, and whose parents are not married under the age of 18. The majority of cases of early marriage are caused by the occurrence of pregnancies outside of marriage, lack of bonding between parents and adolescents, lack of knowledge related to reproductive health, motivation to find an older boyfriend, and often given money for snacks. Early marriage can be prevented by increasing the role of parents in interacting with children to create bonding with children, providing reproductive health education, and efforts to improve family welfare from relevant stakeholders. Keywords: Characteristics, Early marriage, Young women